2004
DOI: 10.1159/000074966
|View full text |Cite
|
Sign up to set email alerts
|

Reoxygenation with 100 or 21% Oxygen after Cerebral Hypoxemia-Ischemia-Hypercapnia in Newborn Piglets

Abstract: We tested if reoxygenation with 100% O2 was superior to 21% O2 after combined cerebral hypoxemia-ischemia-hypercapnia (HIH) in newborn piglets. Twenty-eight piglets were randomized to reoxygenation with 100 or 21% O2 following asphyxia. Asphyxia was induced by ventilation with 8% O2, adding CO2, and temporary occlusion of both common carotid arteries. After 20 min, reoxygenation-reperfusion was started with 21% O2 (HIH 21% group, n = 13) or 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…This result is consistent with the report by A. Solas and co-authors who demonstrated that 30 min of Re-O 2 was superior to Re-Air in restoration of microcirculation in cerebral cortex of piglets following HI-insult (20). This was associated with significant reduction of excitatory amino acids level in the striatum suggestive of more favorable neurologic outcome in Re-O 2 HI-piglets (5).…”
supporting
confidence: 92%
“…This result is consistent with the report by A. Solas and co-authors who demonstrated that 30 min of Re-O 2 was superior to Re-Air in restoration of microcirculation in cerebral cortex of piglets following HI-insult (20). This was associated with significant reduction of excitatory amino acids level in the striatum suggestive of more favorable neurologic outcome in Re-O 2 HI-piglets (5).…”
supporting
confidence: 92%
“…One major difference between birth asphyxia and the present model is that in the former the partial carbon dioxide tension of arterial blood (PaCO 2 ) is elevated. Restoration of cerebral blood flow during reoxygenation differs whether it starts out with a high or as in the present study a relatively low PaCO 2 (16). In resuscitated newborns infants, we also know that the time of reoxygenation often does not last more than a few minutes.…”
mentioning
confidence: 47%
“…Birth asphyxia is associated with fluctuations in CBF in the early post-resuscitation period [21]. Monitoring PCO 2 is not only important to avoid fluctuations in CBF and but also to maintain moderately elevated PaCO 2 during the first minutes of resuscitation to restore CBF [22,23]. In addition elevated PCO 2 may be beneficial and is associated with higher 5 minute apgar scores after moderate acidemia [24].…”
Section: Discussionmentioning
confidence: 99%